1995
DOI: 10.1159/000126848
|View full text |Cite
|
Sign up to set email alerts
|

A Subgroup of LHRH Neurons in Guinea Pigs with Progestin Receptors Is Centrally Positioned within the Total Population of LHRH Neurons

Abstract: Although the role of gonadal steroids in inducing the LH surge is undisputed, the mechanism(s) whereby steroids induce the release of the hypothalamic luteinizing hormone-releasing hormone (LHRH) remain(s) enigmatic. In this study we examined the issue of the presence of steroid receptors in LHRH neurons using a mammalian species that has a true luteal phase, namely, guinea pigs. Progestin receptors (PR) were localized in LHRH neurons of ovariectomized guinea pigs administered estradiol (10–20 µg estradiol ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…Which (if any) of these progesterone-receptive neurons are involved in the inhibitory effects of progesterone on the generation of the GnRH surge and whether they lie within, or impinge upon, the estradiol signal transmission pathway, however, remains to be elucidated. As stated above, although the majority of reports have been unable to locate progesterone receptors within GnRH neurons, it is worthy of note that one group, working in the guinea pig, has consistently found progesterone receptors in a small subpopulation (10%) of GnRH neurons (29), the physiological role of which is unknown. The existence of a similar subpopulation of progesterone receptive GnRH neurons, in the ewe, cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Which (if any) of these progesterone-receptive neurons are involved in the inhibitory effects of progesterone on the generation of the GnRH surge and whether they lie within, or impinge upon, the estradiol signal transmission pathway, however, remains to be elucidated. As stated above, although the majority of reports have been unable to locate progesterone receptors within GnRH neurons, it is worthy of note that one group, working in the guinea pig, has consistently found progesterone receptors in a small subpopulation (10%) of GnRH neurons (29), the physiological role of which is unknown. The existence of a similar subpopulation of progesterone receptive GnRH neurons, in the ewe, cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Previous observations on the morphology [42, 43, 44], the cellular location of steroid receptors [45], or immunocytochemical distribution [3, 46, 47]suggest the presence of distinct populations of GnRH-like cells in the brain of several mammals. However, location of HypGnRH and GnRH in distinct neuronal populations appears unlikely, since both peptides and their respective intermediate precursor forms are synthesized and released [7]by the neuronal GT1 cell line [48].…”
Section: Discussionmentioning
confidence: 99%
“…Several experiments, including electrochemical stimulation (Everett et al, 1964) and deafferentation or lesion studies (Samson and McCann, 1979;Wise et al, 1981;Kalra and Kalra, 1983), have demonstrated that this is an important region for the induction of an LH surge and ovulation. Other studies have suggested that there may exist a primary subpopulation of GnRH neurons localized in this same region that is crucial for producing higher levels of GnRH in times of greater demand, e.g., the LH surge (Rubin et al, 1994;King et al, 1995). This subpopulation of GnRH neurons may be under developmental regulation, and it is quite possible that those neurons that express the NMDA receptor represent a phenotypically distinct subpopulation of GnRH neu- …”
Section: Discussionmentioning
confidence: 99%